Achievement as Gift and Prestige: Formulating Anticipated Emotion of Others as New Determinant of Consumer Motivation - Simamora, Bilson (UI Scholars Hub, 2021)
Emotion is central component of consumer behavior. This concept, that is borrowed from psychology, is now widely and applied studied in marketing. Two major approaches used by marketing researchers are, first, behavior causes emotions and second, emotions cause behavior. In the second approach, marketing researchers study anticipated emotions of the actors and their consequences on the actors¡¯ behavior. The interesting question, how is anticipated emotion of others on the actor¡¯s behavior? This study is purposed to answer that question. The author studies potential emotions of others that accompany future individuals¡¯ achievement when achievement is considered as gift to significant others or prestige source for the individuals. In doing so, the author develops anticipated emotion of others concept, conceptual model, and related propositions. Discussion, direction for further research, and the contributions of the study to the academic and practical worlds are also presented.